Selected aspects of management control in local self-government units - Mituś, Ambroży (Journal of Public Governance, 2018)
The purpose of the article is to discuss a few selected issues related to management control which have not been expressly articulated in the literature on the subject so far. These issues include: a) juridical aspect of management control in order to show the essence and benefits of such control; b) understanding the goals and tasks in the statutory aspect of management control; c) the ensuring nature of management control; d) failure to perform or unsatisfactory performance of management control obligations as grounds for liability, and e) the role of authorities in the management control system as well as others, e.g. the organizational structure of a unit. In this paper, the author consciously forgoes any global presentation of management control, in particular any analysis of the solutions/tools included in the standards of management control, unless they directly refer to the issues discussed. The author uses methods specific for legal sciences, including in particular the method of juridical exegesis of legal texts. Basic conclusions from the analysis are as follows: 1) in the statutory perspective, management control includes a “total of actions” (tools/instruments) of an ensuring nature, and 2) the obligations from the first and second level of management control are performed in a specific local self-government unit by its authorities. Undoubtedly, properly defined management control (i.e. as all ensuring activities) is a useful tool of public management which sets legal regulations along with a particular management model within a given unit of the public finance sector.